Structural dynamic systems computational techniques and optimization : computer-aided design and engineering - Leondes, Cornelius T. (Gordon and Breach international series in engineering, technology, and applied science ;, 1998)
"This volume is a comprehensive treatment of the issues involved in modern seismic design techniques for structures, with a view to significantly enhancing their capability of surviving earthquakes to an adequate degree, i.e., enhancing the ability of structural systems to withstand high-level earthquakes on the Richter scale."--BOOK JACKET. "This book clearly reveals the effectiveness and great significance of techniques available, and, with further development, the essential role they will play in the future."--BOOK JACKET.